2015
DOI: 10.1177/0004867414567758
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of eating disorders in Danish psychiatric secondary healthcare 1970–2008

Abstract: Objective: Is an increased focus on eating disorders during the past few decades reflected by increasing occurrence in the psychiatric health service system. Method:All first-time diagnoses of eating disorders identified in the Danish Central Psychiatric Research Register 1970-2008 constitute the present research database. Age-standardized rates per 100,000 inhabitants were calculated and autoregressive models were fitted for males and females separately as well as for in-and outpatients.Results: The incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Several main (Gammelmark et al, 2015;Lucas, Crowson, O'Fallon, & Melton 3rd., 1999;van Son et al, 2006). Several main (Gammelmark et al, 2015;Lucas, Crowson, O'Fallon, & Melton 3rd., 1999;van Son et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several main (Gammelmark et al, 2015;Lucas, Crowson, O'Fallon, & Melton 3rd., 1999;van Son et al, 2006). Several main (Gammelmark et al, 2015;Lucas, Crowson, O'Fallon, & Melton 3rd., 1999;van Son et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, information on recent time-trends in incidence has been largely derived from psychiatric or primary care registers in four countries, namely Denmark, Sweden, the Netherlands, and the UK (Gammelmark et al, 2015;Holland, Hall, Yeates, & Goldacre, 2016;Javaras et al, 2015;Micali, Hagberg, Petersen, & Treasure, 2013;Steinhausen & Jensen, 2015;van Son, van Hoeken, Bartelds, van Furth, & Hoek, 2006). In Denmark, an investigation of the Danish Central Psychiatric Research Register (DCPR) found an overall increase in AN from 1995 to 2010 in females aged 4-65 years (9.9-19.3/100,000), with the most frequent incidence of AN among girls aged 12-15 years (29.2-61.4/100,000) (Steinhausen & Jensen, 2015), whereas lower and stable incidence rates (IRs) of BN were detected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Eating disorders (EDs)-comprising anorexia nervosa, bulimia nervosa, binge ERED and other specified feeding and ED (American Psychiatric Association, 2013)-are severe mental disorders associated with increased mortality (Arcelus, Mitchell, Wales, & Nielsen, 2011). Register-based studies are important for determining agespecific and gender-specific time trends of ED and have provided important insight into the course and outcomes of ED (Crow et al, 2009;Gammelmark et al, 2015;Javaras et al, 2015;Micali, Hagberg, Petersen, & Treasure, 2013;Steinhausen & Jensen, 2015;Zerwas et al, 2015). However, as the registers are most often based on hospital records, only the most severely affected cases referred to secondary care are included, and hence, the occurrence of ED has been found to be higher in community samples than in register-based studies (Micali et al, 2013;Steinhausen & Jensen, 2015;Zerwas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a review of ED self-management apps found RR to be the most evidence-based and comprehensive app available because of its customizable features and CBT framework (Juarascio, Manasse, Goldstein, Forman, & Butryn, 2015). In addition, an increased number of 15-to 20-year-old individuals are diagnosed with EDs (Gammelmark et al, 2015;Smink, Van Hoeken, & Hoek, 2012;Smink, van Hoeken, & Hoek, 2013), which is an age group consisting of diligent smartphone users, who primarily prefer digital options over analog ones (Pew Research Center, 2017). Furthermore, two studies on blended treatment for patients with depression reported positive outcomes with improved symptom levels (Ly et al, 2015;Zwerenz et al, 2017), and reduced use of clinician time (Ly et al, 2015).…”
mentioning
confidence: 99%